Costs of sustainable forest management in the tropics: State of knowledge - Margret Köthke (Johann Heinrich von Thünen-Institut, 2014)
This report summarises existing knowledge on costs of sustainable forest management (SFM) in tropical and sub-tropical forests. First, the scope of forest-related cost studies and background information on definitions of and obstacles for SFM are given (Sections 1 and 2). The main part of this report gives a review on existing studies about costs of SFM and answers the questions: - What is known about costs of SFM? And who is researching in this field? - How reliable are the existing estimates? - Which research gaps still exist? The different studies' findings are summarised and compared among each other. Furthermore, the coverage and reliability of the existing figures are evaluated. The main question of this report "What are the costs of sustainable forest management in tropical and sub-tropical primary forests?" is not addressed and answered directly by any study. Therefore, studies which tackle part of the problem are included in the review. Section 1.2 gives an overview of the broad scope of forest-related cost studies. Under this scope the studies, which are reviewed in the following, are classified and the study review in this report (Section 3) is structured accordingly. The report concludes on further research needed (Section 4).
urn:nbn:de:gbv:253-201408-dn053660-3
Keywords: 630